Duramesh registry study: short-term outcomes using mesh suture for abdominal wall closure - Hackenberger, Paige N.; Mittal, Mehul; Fronza, Jeffrey; Shapiro, Michael (Frontiers in Surgery, 2024)
Introduction Sutures are flexible linear elements that join tissue and maintain their hold with a surgeon-created knot. Tension at the suture/tissue interface can cut the very tissues that sutures are designed to hold, leading to dehiscence and incisional hernia formation. A new suture design (Duramesh, Mesh Suture Inc., Chicago, IL) was approved for marketing by the United States Food and Drug Administration in September 2022. The multiple filaments of the mesh suture are designed to diffuse tension at the suture/tissue interface thereby limiting pull-through. The macroporosity and hollow core of the mesh suture encourage fibrovascular incorporation for a durable repair. We created the first registry and clinical report of patients undergoing mesh suture implantation to assess its real-world effectiveness. Methods A patient registry was created based on institutional implant logs from January to August 2023 at an integrated health-care system. Operative reports were reviewed by the study team to verify use of “Duramesh” by dictation. Retrospective chart review was conducted to evaluate patient and surgical characteristics, follow-up, and short-term outcomes of interest. Results were analyzed using descriptive statistics and Chi-squared analysis with Microsoft Excel and GraphPad Prism. Results Three hundred seventy-nine separate implantations by 56 surgeons across 12 (sub) specialties at a university hospital and two community hospitals were performed. Mesh suture was used for treatment of the abdominal wall in 314 cases. Follow-up averaged 80.8 ± 52.4 days. The most common abdominal wall indications were ventral hernia repair (N = 97), fascial closure (N = 93), abdominal donor site closure from autologous breast reconstruction (N = 51), and umbilical hernia repair (N = 41). Mesh suture was used in all Centers for Disease Control (CDC) wound classifications, including 92 CDC class 2 or 3 abdominal operations. There were 19 surgical site infections (6.1%) and 37 surgical site events (11.8%). Conclusions Short-term registry data demonstrates the wide diversity of surgical disciplines and scenarios in which mesh suture has been used to date. The early adoption of mesh suture into practice highlights that consequences of suture pull-through influence operative decision making. As this is the first interim report of the Duramesh mesh suture registry, follow-up is too short for characterization of long-term durability of abdominal wall closures.